Increasing Purchasing Decisions on Starbucks Coffee Customers in Depok City Indonesia: Yuaniko Paramitra - Yuaniko Paramitra (Samudra Publisher, 2023)
The purpose of this study was to analyze simultaneously and partially the effect of brand image, product quality on purchase decision Starbucks Coffee consumers in Depok City. Respondents in this study were the consumers of Starbucks Coffee in Depok City, the analytical method used was regression. The results of the study stated that the influence of brand image and product quality on Purchase Decision simultaneously have a significant influence. the influence of brand image on purchase decision partially have a significant influence and the influence of product quality on purchase decision also have a significant influence.